Հայկական Սաթենիկը և նրա կովկասյան զուգահեռները - Ա. Ե. Պետրոսյան (ՀՀ ԳԱԱ հրատ.)
В кавказских эпосах прослеживается влияние армянской мифологии и эпоса: например, образы кадзей, Артавиза и Аргвана в осетинской и западнокавказской традициях имеют армянские прототипы. Имя Сатанa/ Сатаней не этимологизируется на основе осетинского или кавказского языков и не имеет принятой этимологии. Между тем, Сатеник/Сатиник имеет прозрачную армянскую этимологию и образовано от корня сит "гагат, янтарь", с суффиксом -eni (k), ср. аналогичные женские имена Назиник, Арпеник и Варсеник (Х. Ачарян, Т. Далалян). Таким образом, имя Сатана/Сатаней, равно как и ряд имен в кавказских эпосах, восходит к армянской традиции.In Caucasian epics there are traces of influence of Armenian mythology and epic: e.g., the characters of the kadzis, Artawyz and Argwana in Ossetian and Western Caucasian traditions are derived from Armenian prototypes. The name of Satana/Sataney is not etymologized on the basis of Ossetic or Caucasian languages and does not have an accepted etymology. Meanwhile, Satenik/ Satinik has transparent Armenian etymology from the root sat‘ ‘jet, amber’ with the suffix -eni(k), cf. similar female names Nazinik, Arpenik and Varsenik (H. Acharyan, T. Dalalyan). The study of all data shows that the name of Satan/ Satan, along with the mentioned names of Caucasian epics, dates back to the Armenian tradition.
Keywords: Geography; Anthropology; Recreation; Folklore; Ethnology; Social and Cultural Anthropology